Identifying drivers of liking and characterizing the ideal product thanks to Free-Comment. (March 2022) - Mahieu, Benjamin; Visalli, Michel; Schlich, Pascal
Highlights: Drivers of liking can be identified from Free-Comment (FC) data. Ideal-Free-Comment (IFC) enables to characterize the ideal product with FC. IFC enables to locate the ideal product on the FC product map. Drivers of liking based on FC data and IFC are complementary tools. Abstract: Consumers' hedonic appreciation is important for the commercial success of a product. To formulate appreciated products, sensory and hedonic data of some existing products are often linked to each other. Because existing products represent only a limited sensory space of investigation, asking consumers to characterize their ideal product can provide relevant additional information to understand their preferences. First, the paper investigates whether sensory drivers of liking can be derived from linking Free-Comment (FC) and hedonic data. Second, Ideal-Free-Comment (IFC) is introduced. IFC instructs consumers to describe actual products and then their ideal product thanks to FC. IFC paired with liking scoring was used in a home-use test with 483 consumers each evaluating from 1 to 14 (5.71 on average) cooked hams from a list of 30 hams representative of the French market. Based on a mixed linear model, relevant drivers of liking were identified from FC data. The panel's average ideal product was consistent with the drivers of liking. Since descriptors with opposite meanings characterized individual ideal products, a consumer segmentation based on their ideal product was performed and resulted in two segments. The two segments' ideal products mainly differed regarding their flavor. Drivers of liking and the ideal product of the smaller segment ( ≈ 15% of the consumers) were not well consistent suggesting this was a noise segment. Drivers of liking based on FC data and IFC are complementary tools to understand consumers' hedonic appreciation without the use of a pre-established list of descriptors.